INTEGRASI PRINSIP TOTAL QUALITY MANAJEMEN DENGAN HASIL PENILAIAN EVALUASI DIRI MADRASAH: SUATU STRATEGI MEWUJUDKAN PENDIDIKAN BERKUALITAS - Janna, Niftahul; Bahrani, Bahrani; Ramli, Akhmad (STKIP Pesisir Selatan, 2024)
Education plays a strategic role in building quality human resources. An effective and efficient education management system is needed in accordance with the principles of Total Quality Management (TQM). This study aims to analyze the integration of the application of Total Quality Management (TQM) principles with the results of Madrasah Self Evaluation (EDM) assessment as a strategy to realize quality education. This research uses a qualitative method that takes data from a literature review of recent scientific articles related to the principles of TQM and the implementation of EDM. The results show that TQM principles-customer satisfaction, comprehensive involvement, and continuous improvement-can be effectively operationalized through data-based EDM applications. Although the integration of TQM principles with data-based technology such as EDM has not been widely explored empirically in madrasahs, data-based management is considered necessary to be the main foundation of TQM implementation in the madrasah environment. As EDM is one of the tools to support TQM in education, this research seeks to explore the relationship in the context of educational evaluation. The results of this study are expected to make a theoretical contribution to education management.